The radial augmentation index in children with Kawasaki disease without acute coronary artery lesions during the convalescent period - Zheng J; Nakamura T; Lu N; Hori K; Oguri M; Sakurai M; Ishizaki M (Dove Medical Press, 2019)
Jianbo Zheng,1,2 Tsuneyuki Nakamura,1 Na Lu,1,2 Kaori Hori,1 Masato Oguri,1 Masaru Sakurai,3 Masao Ishizaki31Department of Pediatric Cardiology, Kanazawa Medical University, Ishikawa, Japan; 2Department of Pediatrics, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of China; 3Department of Hygiene, Kanazawa Medical University, Ishikawa, JapanPurpose: We recently reported that children and adolescents with a history of Kawasaki disease (KD) had slight but significant elastic arterial stiffness even when no coronary artery lesions (CALs) were present. Moreover, we hypothesized that KD-related arteriopathy may also cause peripheral artery dysfunction. The objective of this study was to assess the involvement of radial artery pulse waves, especially reflection waves from the peripheral arteries using the radial artery augmentation index (rAI) in patients without CALs after KD. Materials and methods: We first collected the rAI data from 312 subjects (149 consecutive patients of KD and 163 control subjects). Next, 225 cases between 6 and 15 years old were selected. Finally, 41 pairs were included for analysis. The rAI values of these two groups were compared and analyzed. Acute-phase data were also collected to reveal the possible correlation with rAI in the convalescent period. Results: Multivariable analysis revealed the history of KD was positively correlated with rAI@75 value in children from 6 to 15 years old. After pairing the height and gender, the KD group also had significantly higher rAI and rAI@75 than the control group (rAI 60.63±13.77 vs 54.56±13.17, p=0.028; rAI@75 63.61±15.21 vs 55.68±14.86, p=0.003). With regard to acute-phase condition, nonresponse to initial treatment was also linked to elevated rAI during the convalescent period. Conclusions: During the convalescent period, the rAI increased in KD patients without acute CALs. Furthermore, nonresponse to initial treatment in acute phase conferred higher rAI to KD subjects than respondent cases. Elevated rAI means the reflection wave from the peripheral vascular is stronger or earlier. This small but significant change may indicate the existence of peripheral artery stiffness during the convalescent period.Keywords: Kawasaki disease, augmentation index, peripheral artery stiffness